Improving patient-clinician communication following nephrectomy in renal cell carcinoma: Development, content validation and pilot testing of a conversation aid tool. Issue 1 (January 2021) - Bentley, Sarah; Johnson, Chloe; Exall, Elizabeth; Brohan, Elaine; Lawrance, Rachael; Bennett, Bryan; Bargo, Danielle; Zanotti, Giovanni; Staehler, Michael; Stewart, Grant D
Highlights: Unlike decision aids, Conversation Aid Tools (CATs) support patient/clinician conversations. A CAT was developed for renal cell carcinoma (RCC) patients. Interviews verified that the CAT was understood and relevant to RCC patients. Reviewing the CAT improved patient knowledge of RCC when compared to the standard of care. Patients indicated that they would feel confident discussing RCC using the CAT. Abstract: Objectives: This study developed, and established the content validity, of a conversation aid tool (CAT) for use in clinical practice with renal cell carcinoma (RCC) patients who receive a curative nephrectomy and are at high-risk of recurrence. The CAT was pilot tested in a sample of RCC patients to establish whether the CAT increases knowledge of RCC, treatment options (such as adjuvant therapy), and care options. Methods: A cross-sectional, mixed methods design was used involving initial, exploratory interviews with RCC patients, RCC specialists and a steering group. Further content validation interviews were conducted with RCC patients and specialists. A web-based survey was conducted with RCC patients (N = 60), to compare the CAT versus a standard of care (SOC) consultation comparator tool on patient knowledge. Results: Findings from exploratory interviews were used to develop the CAT. Content validation interviews demonstrated that the CAT was well understood and relevant to RCC patients. The web-based survey demonstrated that viewing the CAT significantly improved participants knowledge of RCC, and care options, when compared to the SOC. Conclusion: The findings highlight that the CAT is a relevant, comprehensive and well-understood tool for use in the post-nephrectomy consultation. Practice implications: Use of the CAT may increase patient knowledge of RCC and care options.